Digital advances in medicine, e-health, and communication technologies - Rodrigues, Joel 1972- (Medical Information Science Reference, 2013)
"This book explores the developments and trends in medical informatics and their approaches toward telemedicine and e-health applications" - Provided by publisher
Includes bibliographical references and index
Keywords: Aufsatzsammlung